WALi: Nested-Word Automata - Driscoll, Evan; Thakur, Aditya; Burton, Amanda; Reps, Thomas (University of Wisconsin-Madison Department of Computer Sciences, 2011)
WALi-NWA is a C++ library for constructing, querying, and operating on nested-word automata. It is a portion of the WALi library, which provides types and operations for weighted automata. While the NWA portions of WALi are mostly logically separate from the rest of WALi, it does use facilities provided by WALi and inter-operates with WALi's weighted pushdown system (WPDS) code.